Reducing temporal tensions as a strategy to promote sustainable behaviours. (September 2016) - Oliveira, Luis; Mitchell, Val; May, Andrew
Abstract: This research proposes that it is possible to deliberately reduce temporal tensions in order to promote energy saving behaviours. People may not dedicate enough time to planning their tasks that consume energy, rushing into them without much deliberation. They may also use more energy than necessary in an attempt to accelerate processes that seem to be taking too long, to reduce the boredom of waiting. Persuasive technology provided the tools to manipulate the perception of time and therefore elicit changes in the specific behaviours that result in unnecessary energy usage. Cooking tasks were used as the scenario to test behaviour change strategies delivered via a smartphone application. Results showed that these strategies facilitated the performance of sustainable behaviours. Participants reported that the app made (1) them more likely to follow the steps needed to use less energy, (2) the activity more enjoyable and (3) the time appear to pass more quickly compared to a control version. Highlights: Temporal tensions can cause people to use more energy than needed. A smartphone application was developed to manipulate perceptions of time. Cooking behaviours were chosen as the platform for evaluating this intervention. Participants tested the application as an assistant for a cooking task. The app made participants more likely to follow the energy saving techniques.